EFEKTIVITAS PERASAN DAUN SIRIH HIJAU (Piper betle) SEBAGAI BAHAN ANESTESI ALAMI PADA INDUK UDANG GALAH (Macrobrachium rosenbergii) - Mudaza, Iqbal; Rosmaiti, Rosmaiti; Putriningtias, Andika (Universitas Teuku Umar, 2020)
Shrimp is a type of crustacean biota that lives in fresh, brackish and marine waters. Giant prawns are also freshwater shrimp that have high economic value, and are a fishery commodity that is widely observed by local and foreign consumers. Consumer demand for shrimp commodities has experienced a shift towards meeting the need for live shrimp. One of the methods used in the process of optimally transporting shrimp is to perform shrimp anesthesia with the aim to maintain the fiological and morphological conditions of the shrimp, so that the shrimp is expected to arrive in a state of life by using green betel leaf extract. The design used in this study is complete randomized design (CRD) consisting of 4 treatments with 5 replications namely in the treatment of 1 immersion at a dose of 50 ml / 4 liters of water, 2 immersion treatment at a dose of 100 ml / 4 liters of water, 3 immersion treatment at a dose of 150 ml / 4 liters water and 4 immersion treatment with a dose of 200 ml / 4 liters of water. Based on the results of the study, it can be concluded that the difference in the dose of green betel leaf extract significantly affects the time of fainting and conscious time of giant prawns, the best dose that can be given to shrimp as an anesthetic during transportation dry system for ± 6 hours is treatment 4 namely with ex dose betel leaf powder 200 ml / 4 L water.